Patient-centered outcome measures comparing the autogenous and allogenic bone blocks in the augmentation of deficient alveolar ridges: A pilot study - Pranjali Vijaykumar Bawankar; Abhay Pandurang Kolte; Rajashri Abhay Kolte (Wolters Kluwer Medknow Publications, 2023)
Background: The aim of the present study was to evaluate and compare the patient-reported experience and outcome measures (PREMS and PROMS) and three-dimensional augmentation efficacy of the autogenous and allogenic bone block grafts in deficient alveolar ridges through cone beam computed tomography (CBCT). Materials and Methods: Twenty patients were equally divided into Groups I and II treated with autogenous and allogenic bone block grafts for ridge augmentation, respectively. The radiographic parameters including the apico-coronal defect height (DH) as well as buccolingual defect depth (DD) and mesiodistal defect width (DW) at apical, middle, and cervical zone were measured using CBCT at baseline, 6 months and 1 year. The PREMS and PROMS were evaluated using Visual analogue scale (VAS) scale and questionnaire method. Results: The mean DH, apical DD and DW, middle and cervical zone DW were significantly different between two study groups (P < 0.05). The mean apical 11.6 ± 1.91 and middle zone 9.43 ± 0.89 DD were significantly higher (in Group I as compared to Group II, with P values 0.016 and 0.004, respectively). The mean bone gains in apico-coronal DH and mesio-distal DW dimension in the apical and middle zone was significantly higher in Group I (P < 0.0001). The comparison of PROM revealed better patient satisfaction in Group II as depicted by significantly higher VAS score (P < 0.0001). Conclusion: Superior bone gain and reduced graft resorption was observed in Group I when compared to Group II. On the contrary, better PROMs and PREMs were obtained with the allogenic bone block augmentation.